2014
DOI: 10.1016/j.stem.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Imaging: From Bench to Bedside

Abstract: Although cellular therapies hold great promise for the treatment of human disease, results from several initial clinical trials have not shown a level of efficacy required for their use as a first line therapy. Here we discuss how in vivo molecular imaging has helped identify barriers to clinical translation and potential strategies that may contribute to successful transplantation and improved outcomes, with a focus on cardiovascular and neurological diseases. We conclude with a perspective on the future role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
248
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(249 citation statements)
references
References 111 publications
(161 reference statements)
1
248
0
Order By: Relevance
“…One is to transfect the cells with a reporter gene 2,7 and follow-up on their proliferation through optical imaging, positron emission tomography or magnetic resonance imaging [8][9][10] . This strategy, however, requires a rather time-consuming transfection procedure that may lead to undesired phenotypical alterations and abnormalities in the transplanted cells in comparison to the native cells [11][12][13] . The second strategy is to label the cells with exogenous contrast agents, being either organic probes or inorganic nanoparticles (NPs) 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…One is to transfect the cells with a reporter gene 2,7 and follow-up on their proliferation through optical imaging, positron emission tomography or magnetic resonance imaging [8][9][10] . This strategy, however, requires a rather time-consuming transfection procedure that may lead to undesired phenotypical alterations and abnormalities in the transplanted cells in comparison to the native cells [11][12][13] . The second strategy is to label the cells with exogenous contrast agents, being either organic probes or inorganic nanoparticles (NPs) 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanotechnologies have contributed to advances in in vivo high-resolution imaging to monitor stem cells and exosomes tracking and homing, providing useful insights in their mechanism of action. [18][19][20][21][22][23] To produce a detectable change in signal intensity, cells or exosomes must be labeled with magnetic resonance (MR) contrast agents. In this regard, superparamagnetic iron oxide nanoparticles, which are small crystalline magnetite structures ranging in size from 5 nm to 150 nm, have been widely used to magnetically label stem cells and exosomes.…”
mentioning
confidence: 99%
“…Stem cell therapies provide unique opportunities for diseases of the Central Nervous System [12][13][14]. By co-transplantation of BMSCs and embryo Olfactory Ensheathing Cell (OECs) in vivo, we confirmed that spinal nervous cells conduction performance improved and the histological analysis suggested that the BMSCs differentiating into neurons cell proportion increased significantly.…”
Section: Editorialmentioning
confidence: 64%